بنية الزمن في مجموعة مجاز السَّرو القصصية لـ عبد الوهاب عيساوي - حميد, الرائسة; عتيقة, حنان (جامعة الوادي - University of Eloued, 2023)
طغت على شخوص مجاز السرو نبرة الوحدة القاتلة وهي الميزة والثيمة الكبرى لهذه التجربة القصصية واعتماد الكاتب عبد الوهاب عيساوي لتقنية الاسترجاع بكثرة وهذا مادل على شيء فإنه يدل أن هذه الشخوص ذات طابع سيكولوجي عميق ، لأنها عائشة في الزمن الماضي غارقة فيه. Study summary The characters of the cypress metaphor were dominated by the tone of fatal loneliness, which is the great feature and theme of this narrative experience, and the author Abdel-Wahhab Al-Issawi's adoption of the retrieval technique in abundance, and this indicates something, as it indicates that these characters have a deep psychological nature, because they live in the past tense immersed in it.
Keywords: مجاز السرو،المجموعة القصصية، الزمن، السرد; metaphor of cypress, story collection, time, narration